The Multi-Structural Model of Speech and Language Development in the Aspect of Holistic Approach - Tomele, Gundega (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article analyses the theories on the child's language acquisition and development process (psychological nativism, cognitivism, interactionism, bihaviorism), and it is concluded that the various models of language acquisition raised in these theories depend on language development stage and its representative factors - the dominant neural processes, language acquisition strategies and the results in a context of language development. Speech and language development and their interconnection can be viewed inthe aspect of holistic approach - how it is affected by diverse exogenous and endogenous factors, the development of language basis’ functions and the varied mutual interaction of all the factors mentioned above. There is the multi-structural language development model diverse in each individual case and thus defining the individual character of child’s language development process and language disorder adjustment.